Strategi Orang Tua Dalam Menstimulasi Resiliensi Pada Anak Usia Dini - Ekaningtyas, Ni Luh Drajati; Wiguna, Ida Bagus Alit Arta (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
Various challenges and unpleasant conditions that are present in life require us to have adequate resilience in order to be able to cope well with various challenges and obstacles in life and avoid various psychological disorders that can be detrimental. Adequate resilience will enable individuals to carry out their various life roles optimally without compromising their mental health. Therefore, resilience needs to be developed from an early age so that children are used to dealing with various developmental challenges in a healthy manner. This research is a descriptive qualitative research that aims to analyze the strategies applied by parents in stimulating resilience in early childhood. The subjects in this study were fifteen pairs of parents and 18 early childhood who live in Mataram City, West Nusa Tenggara. Data collection is done by interview, observation, and documentation. Parents stimulate early childhood resilience with strategies of providing understanding, motivation, role modeling, and freedom to children with the aim of fulfilling children's basic safety needs, meeting children's educational needs, developing children's friendship skills, facilitating the development of children's interests and talents, introducing various positive values ​​to children. children, and instill various social competencies in children. These various strategies can support children to grow into resilient individuals so that they can carry out their various developmental roles and tasks in a healthy and reasonable manner. Individuals with good resilience will also have good self-control so that they will become intellectually and emotionally intelligent individuals.